2023
DOI: 10.1111/cbdd.14295
|View full text |Cite
|
Sign up to set email alerts
|

Coptidis rhizoma and evodiae fructus against lipid droplet deposition in nonalcoholic fatty liver disease‐related liver cancer by AKT

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease in the world. NAFLD has become one of the major factors contributing to hepatocellular carcinoma (HCC) development. However, there are no clear targets and therapeutic drugs for NAFLD‐related liver cancer. This study explored the active compounds, target and mechanism of coptidis rhizoma and evodiae fructus in the treatment of NAFLD‐related liver cancer based on the network pharmacology and experimental verification. There were 455 inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Thus, the expression of CPT1α was up-regulated, the function of mitochondrial fatty acid βoxidation was enhanced, and finally, the steatosis of hepatocytes was improved Li, Li, Yang, et al, 2022). In addition, our previous studies also found that quercetin can improve lipid deposition in HepG2 cells by reducing the phosphorylation level of AKT (Li et al, 2023).…”
Section: Quercetinmentioning
confidence: 87%
“…Thus, the expression of CPT1α was up-regulated, the function of mitochondrial fatty acid βoxidation was enhanced, and finally, the steatosis of hepatocytes was improved Li, Li, Yang, et al, 2022). In addition, our previous studies also found that quercetin can improve lipid deposition in HepG2 cells by reducing the phosphorylation level of AKT (Li et al, 2023).…”
Section: Quercetinmentioning
confidence: 87%